The Student's Relationship with Teacher and His Relation to the Student's Behavior in the Intermediate Stage Students - ايمان صادق عبد الكريم (College of Education for Women, 2019)
The goal of this study is to investigate the relationship between the student and the teacher and the student's behavior for a subject of the student in the intermediate stage, the sample contained (568) student, (266) male and (302) female. The scale of student - teacher relationship was built according to a questionnaire pointed to a sample of the students, adding to that reviewing a number of previous scales and studies which was about the same topic, and in the same way a measure of student behavior was constructed. Results showed that there was significant relation between the student's teacher relationship and student behavior, and the level of student- teacher relationship is higher than the average of the population that is there a positive relationship ,as well as the level of student behavior is higher than the average of the population ,that is their behavior is positive, also results showed that there were no significant differences in student-teacher relationship and student behavior in individuals based on gender. Key words: (1)Student _teacher relationship (2)Student behavior